The Omni Scale Is Not Suitable for Assessing Self-Perceived Exertion during Physical Activity in Preschoolers - Carlos Ayán; José C. Diz; Silvia Varela; Miguel A. Sanchez-Lastra (MDPI AG, 2023)
Introduction: We aimed to identify the utility, reliability, and validity of an adapted version of the OMNI self-perceived exertion (PE) rating scale in preschoolers. Population and methods: Firstly, 50 (mean age ± standard deviation [SD] = 5.3 ± 0.5 years, 40% girls) performed a cardiorespiratory fitness (CRF) test twice, with a one-week interval between assessments, and rated their PE either individually or in groups. Secondly, 69 children (mean age ± SD = 4.5 ± 0.5 years, 49% girls) performed two CRF tests, separated by a one-week interval, twice and rated their self-PE. Thirdly, the heart rate (HR) of 147 children (mean age ± SD = 5.0 ± 0.6 years, 47% girls) were compared against self-rated PE after finishing the CRF test. Results: Self-assessed PE differed when the scale was administered individually (e.g., 82% rated PE with 10) or in groups (42% rated PE with 10). The scale showed poor test-retest reliability (ICC:0.314-0.031). No significant associations were found between the HR and PE ratings. Conclusions: An adapted version of the OMNI scale was found not suitable for assessing self-PE in preschoolers.